Crossing the River Magra in the 'land of broken bridges': risk in early nineteenth-century travel narratives. Issue 9 (2nd September 2019) - Balzaretti, Ross
Abstract: On the 25 October 2011 the River Magra in the far east of the Italian region of Liguria flooded with catastrophic effects, killing thirteen people and causing millions of euros in damage. Managing such an extreme episode is very hard, as local policy makers know well because the Liguria region is currently experiencing regular flood events. Serious floods in this region have often occurred seasonally in October and November as the result of extremely intense rainfall. While everyone can agree that rivers in flood present real environmental risks to human life it is important to appreciate that risk can also be in the mind. Understanding how people deal with environmental risk in this respect can help inform current policy, for example what tactics might best be used to persuade people to leave their homes when flood events are forecast. This article shows how reading a series of reports by early nineteenth-century travellers who tried to cross the Magra in flood reveals that perceptions of risk had a considerable impact on their behaviour in the face of a clear environmental problem. Furthermore, because these written accounts were consumed by a reading public back home which enthusiastically embraced narratives of travel, especially ones which dealt with what has come to be known as 'dark tourism' (i.e. delighting in danger), we can learn how telling stories might still be an important or even necessary part of successful risk management in the future.